2017
DOI: 10.1186/s12955-017-0706-9
|View full text |Cite
|
Sign up to set email alerts
|

The association between physical activity and health-related quality of life among breast cancer survivors

Abstract: BackgroundThe quality of life for breast cancer survivors has become increasingly important because of their high survival rate and prolonged life expectancy. The purpose of this study was to examine the association of physical activity following diagnosis and health-related quality of life (HRQOL) in breast cancer survivors.MethodsWe conducted a cross-sectional study of breast cancer survivors. A total of 231 women aged 21–78 years who had been diagnosed with stages I to III breast cancer and had breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 46 publications
6
42
0
3
Order By: Relevance
“…The findings of the present study are consistent with our previous research and other observational studies [3][4][5]23,24,26,35,36]. We found that Korean breast cancer survivors with greater adherence to the ACS guidelines had higher levels of social functioning, which was assessed by a validated Korean version of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30) [24].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of the present study are consistent with our previous research and other observational studies [3][4][5]23,24,26,35,36]. We found that Korean breast cancer survivors with greater adherence to the ACS guidelines had higher levels of social functioning, which was assessed by a validated Korean version of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30) [24].…”
Section: Discussionsupporting
confidence: 91%
“…We found that Korean breast cancer survivors with greater adherence to the ACS guidelines had higher levels of social functioning, which was assessed by a validated Korean version of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30) [24]. In our previous cross-sectional study, higher physical activity levels were associated with a better quality of life in terms of fatigue, pain, and sexual functioning among Korean women who had been diagnosed with breast cancer [5]. In another cross-sectional study that we conducted, two dietary patterns, the healthy dietary pattern and the Western dietary pattern, were empirically derived using factor analysis among Korean breast cancer survivors, and higher healthy dietary pattern scores were associated with decreasing dyspnea and increasing insomnia scores [35].…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with randomized controlled trials that have shown increases in PA with simultaneous increases in HRQOL [19,20,21,22]. These findings are further supported by studies that have shown increased HRQOL in physically active participants with chronic diseases [23][24][25][26][27][28][29]. Finally, these results are consistent with studies that have shown significant relationships between PA and HRQOL among rural adults suffering from chronic illness [30,31].…”
Section: Odds Ratios (Ors)supporting
confidence: 89%
“…Recent advances in prevention, screening, and treatment have resulted in longer survival for cancer survivors, particularly those diagnosed with early‐stage disease . However, a significant proportion of these survivors continue to experience decrements to health‐related quality of life (HRQOL) even years after the completion of their cancer treatment, including chronic pain, fatigue, sexual dysfunction, and psychosocial concerns such as depression, anxiety, and decreased social support . Compared with non‐Latino whites (NLWs), Latinos face disproportionately higher mortality and worse HRQOL after the diagnosis and treatment of the 3 most common nonskin cancers: prostate, breast, and colorectal cancer .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 However, a significant proportion of these survivors continue to experience decrements to healthrelated quality of life (HRQOL) even years after the completion of their cancer treatment, [4][5][6][7][8][9] including chronic pain, fatigue, sexual dysfunction, and psychosocial concerns such as depression, anxiety, and decreased social support. 3,[10][11][12][13][14][15][16][17][18][19][20] Compared with non-Latino whites (NLWs), Latinos face disproportionately higher mortality and worse HRQOL after the diagnosis and treatment of the 3 most common nonskin cancers: prostate, breast, and colorectal cancer. [21][22][23][24][25][26] Latinos are also more likely to have less educational attainment, live below the federal poverty level, and lack both health insurance and a primary care provider in comparison with NLWs.…”
Section: Introductionmentioning
confidence: 99%